Legal Certainty on Business Dispute Resolution Through Arbitration - Christina Bagenda; Anindya Bidasari; Purwanto; Bambag Teguh Handoyo; Rustam (Universitas Muhammadiyah Palu, 2025)
Arbitration has increasingly become the preferred method for resolving business disputes, offering an alternative to the often lengthy and complex litigation process. It presents several advantages, such as expedited proceedings, confidentiality, and final, binding decisions. This article explores how legal certainty is upheld within the arbitration process and evaluates its effectiveness in resolving commercial disputes in Indonesia. The research adopts a normative juridical method, utilizing qualitative analysis of legislation, legal doctrines, and case studies of arbitration awards. The findings indicate that Indonesia’s arbitration framework, governed by Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, provides a solid legal foundation for arbitration proceedings. The final and non-appealable nature of arbitration decisions enhances legal certainty for the disputing parties. Nevertheless, challenges remain in the enforcement phase, particularly in the execution of arbitral awards through the district courts. These issues highlight the need for better coordination between arbitration institutions and the judiciary, along with improved legal awareness among law enforcement officials regarding the role of arbitration. In conclusion, arbitration continues to play a vital role in ensuring legal certainty and promoting the efficient resolution of business disputes in today’s legal landscape.